DIGITAL TRANSFORMATION AND PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES: EMPIRICAL EVIDENCE IN PARIAMAN CITY - Wijaya, Reni; Yadewani, Dorris; Wati, Henny (JURNAL DIMENSI, 2024)
In this digital age, digital transformation has become a challenge for many businesses, especially SMEs. Small and medium-sized enterprises (SMEs) are projected to benefit from digital transformation. The study will look at how digital transformation affects SME performance in Pariaman City. The study employs quantitative methodologies, namely double linear regression analytic techniques. The research data was gathered via a survey of 100 SMEs in Pariaman City. The study found that digital transformation had no substantial positive influence on SME performance. The findings of this study imply that digital transformation cannot be a one-stop solution for boosting the performance of SMEs. Governments should provide more assistance to SMEs in implementing digital transitions. SME actors must develop their digital abilities in order to make the best use of digital technologies. This study is designed to help the development of SMEs in Pariaman City and better understanding of the influence of digital transformation on SME performance.